The determinants of financial distress in Malaysian construction sector / Muhammad Danial Azalan and Nur Zulaiqa Abd Rahman - Azalan, Muhammad Danial; Abd Rahman, Nur Zulaiqa (Faculty of Business and Management, 2016)
The objective of this study is to identify the determinants of financial distress in Malaysian construction sector. The dependent variable of this study is time interest earned while the independent variables are debt to capital, working capital and sales index. The type of data used in this study is panel data. The sample of study consists of 67 companies in the construction sector and data collected cover the period from 2001 until 2015. This study employs Panel Regression Fixed Effect Model in order to study the relationship between those variables. The result of this study shows that debt to capital, working capital and sales index has significant relationship with financial distress. In conclusion, it will be important determinants to use in to see the financial distress in the construction industry.